Escola vista pelas crianças: uma análise das representações sociais da escola na voz (vozes) das crianças - Souza, Erenice Jesus de (2011)
With the advent of Law No. 11.274/06 a new order is established in the structure and operation of Basic Education in Brazil: the school for nine years duration with the inclusion of children six years old. This new reality leads to reflections on the school as a locus of observation of the relationships established therein and challenges researchers from various fields to devote special attention to understanding the child as a subject of rights and full social actor count for much with the reading their looks and voices that can significantly facilitate the improvement of the quality of education as a subjective public right. In this sense, this research aims to contribute reflections about how children perceive the universe of social representations called school, socio-historical situating it as an object to be investigated. Through the research methodology and qualitative approach in education, we selected a group of children enrolled in the first years of elementary education at a public school in the outskirts of São Paulo and use the techniques of semi-structured interviews with small groups and participant observation obtained major centers of thought and identify the significant elements of content analysis. Based on studies conducted by Pierre Bourdieu, Lev Vygotsky, William Corsaro, Sylvia Lane, Serge Moscovici and Laurence Bardin, among others, this reflection implies a concrete analysis of social representations that the individual has the world around him, the child in relation to school, immersed in a speech quite broad, where the gaps, contradictions and ideology could be detected